2018
DOI: 10.3324/haematol.2018.193243
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing diagnostic biomarkers of iron deficiency anemia in community-dwelling Indian women and preschool children

Abstract: The detection of iron deficiency anemia is challenged by the paucity of diagnostic tests demonstrating high sensitivity and specificity. Using two biomarkers, zinc-protoporphyrin/heme and hepcidin, we established the diagnostic cut-off values for iron deficiency anemia in preschool children and women. We randomly selected non-anemic individuals (n=190; women=90, children=100) and individuals with iron deficiency anemia (n=200; women=100, children=100) from a preexisting cohort of healthy preschool children and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…However, no additional predictive benefit was found even when paired with levels of haemoglobin, but rather overestimated ID prevalence relative to standard cut-off points (> 52 μmol / mol haeme). These findings from our study is consistent with other MNP studies that used ZPP as additional iron indicator [31,47,48], but contrary to other MNP intervention findings [31,49]. This may be attributed to the differences in ZPP cut-offs used to define iron deficiency, which was lower in our study (> 52 μmol / mol of haeme) compared to a study in Zanzibar (> 80 μmol / mol of haeme) [31,49,50].…”
Section: Plos Onesupporting
confidence: 83%
“…However, no additional predictive benefit was found even when paired with levels of haemoglobin, but rather overestimated ID prevalence relative to standard cut-off points (> 52 μmol / mol haeme). These findings from our study is consistent with other MNP studies that used ZPP as additional iron indicator [31,47,48], but contrary to other MNP intervention findings [31,49]. This may be attributed to the differences in ZPP cut-offs used to define iron deficiency, which was lower in our study (> 52 μmol / mol of haeme) compared to a study in Zanzibar (> 80 μmol / mol of haeme) [31,49,50].…”
Section: Plos Onesupporting
confidence: 83%
“…Hanoun et al showed that MLL-AF9induced AML cells disrupt bone marrow HSC niche function through alteration of the niche compartments and decrease of the expression of MSC-derived Cxcl12, Scf, Vcam1, and increased expression of Opn. 15 These phenotypes in the MLL-AF9-induced AML bone marrow niche mirrored those in the Twist1-deficient bone marrow niche observed by Liu et al 2 They also found that a Twist1-deficient niche promoted progression of MLL-AF9-induced AML. By using RNAsequencing, the authors found that Jagged-2 is significantly increased in the stromal cells from the Twist1-deficient bone marrow niche and that Notch receptors are upregulated on leukemia cells.…”
supporting
confidence: 60%
“…However, iron deficiency and other conditions associated with anemia, such as the anemia of chronic disease and hemoglobinopathies often coexist, requiring further refinement of diagnostic strategies. The study reported by Kanuri et al 2 in this issue represents an effort to opti-mize diagnostic biomarkers of iron deficiency anemia employing erythrocyte zinc-protoporphyrin/heme ratio (ZPP/H) and serum hepcidin measurements.…”
Section: Assessment Of Iron Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact differentiating iron deficiency from normal iron status in inflammatory context is of great complexity association of other tests is currently examined and studied worldwide [25][26][27][28][29].…”
Section: Ferritin and Various Factorsmentioning
confidence: 99%